Iron Age Nebo: Preliminary investigations at Khirbat al-Mukhayyat and Rujm al-Mukhayyat, Jordan - Danielson, Andrew (Palestine exploration quarterly, 2021)
Recent archaeological investigation at Khirbat al-Mukhayyat and nearby Rujm al-Mukhayyat in west-central Jordan have sought to determine the nature and date of Iron Age activity at these sites. Identified as the Nebo of biblical tradition and the Mesha Inscription, Khirbat al-Mukhayyat fulfilled a strategic role within the region. Positioned at the western edge of the Transjordanian plateau, the site holds a commanding view of the Jordan Valley and Judean highlands to the west, enabling inhabitants to monitor access to and from the Jordan Valley, as well to take advantage of agricultural opportunity within the region. This strategic position is reflected in Mukhayyat’s contested history under Israelite, Moabite, and eventually Assyrian control. With significant contexts dating to the Iron IIB and Iron IIC at Khirbat al-Mukhayyat, and late Iron Age/Persian period activity at the Rujm al-Mukhayyat, this paper presents the preliminary results of excavation and survey efforts together with ceramic data, providing an important contribution to the study of the Iron Age in this region.